2012
DOI: 10.1016/j.bbrc.2012.05.031
|View full text |Cite
|
Sign up to set email alerts
|

S-layer proteins of Lactobacillus acidophilus inhibits JUNV infection

Abstract: It has been previously described that S-layer binds to the C-type lectin DC-specific ICAM-3-grabbing nonintegrin (DC-SIGN, CD209). It was also shown that DC-SIGN is a cell-surface adhesion factor that enhances viral entry of several virus families. Among those, Junin virus (JUNV) entry is enhanced in cells expressing DC-SIGN and for that reason surface-layer protein (S-layer) of Lactobacillus acidophilus ATCC 4365 was evaluated as a possible JUNV inhibitor. Experiments using 3T3 cells stably expressing DC-SIGN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…Moreover, L. helveticus R0052 has a surface layer protein (SlpA), and JohnsonHenry et al (32) showed that the S layer from R0052 inhibited enterohemorrhagic Escherichia coli O157:H7 adhesion to IECs. Martinez et al (33) have reported that treatment with the S layer was able to inhibit viral infection in dendritic cells; however, the inhibition was contingent upon the S layer being used in the early stages of viral infection and not after. Recently, Taverniti et al (34), using an in vitro model of IECs (Caco-2), reported that the strain L. helveticus MIMLh5 and its S-layer protein induced antiinflammatory effects by reducing the activation of NF-B.…”
Section: Applied and Environmental Microbiologymentioning
confidence: 99%
“…Moreover, L. helveticus R0052 has a surface layer protein (SlpA), and JohnsonHenry et al (32) showed that the S layer from R0052 inhibited enterohemorrhagic Escherichia coli O157:H7 adhesion to IECs. Martinez et al (33) have reported that treatment with the S layer was able to inhibit viral infection in dendritic cells; however, the inhibition was contingent upon the S layer being used in the early stages of viral infection and not after. Recently, Taverniti et al (34), using an in vitro model of IECs (Caco-2), reported that the strain L. helveticus MIMLh5 and its S-layer protein induced antiinflammatory effects by reducing the activation of NF-B.…”
Section: Applied and Environmental Microbiologymentioning
confidence: 99%
“…We propose, for biotechnological applications, that pre-growth of lactobacilli in high-salt conditions would result in an advantage for the probiotic nature of cells: the increased production and release of the S-layer might be appropriate for their antimicrobial capacity (Prado-Acosta et al 2008Martínez et al 2012;Meng et al 2015). Also, the reduction of the LTA content needs to be evaluated for possible anti-inflammatory (Kim et al 2014;Kaji et al 2010) or inflammatory effects (Lebeer et al 2012;Mohamadzadeh et al 2011;Zadeh et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…S-layers are arrays of a single protein that constitutes the outermost cell envelope and have been considered to function as protective coats, maintenance of cell shape, and adhesion to specific hosts (Avall-Jääskeläinen and Palva 2005; Hynönen and Palva 2013;Gerbino et al 2015). In addition, we have recently shown that the S-layer of Lactobacillus acidophilus has antibacterial endopeptidase activity and antiviral functions (Prado-Acosta et al 2008Martínez et al 2012). S-layer proteins are present in some Lactobacillus species that are normal inhabitants of the oral and genital cavities and the gastrointestinal tract (GIT) of humans and animals and that are generally recognized as safe (GRAS).…”
Section: Introductionmentioning
confidence: 97%
“…SLPs were believed to play an important role in most of the probiotic properties of L. acidophilus strains, such as helping L. acidophilus adapt to a hostile environment, mediating the adherence of L. acidophilus strains to intestinal epithelial cells, regulating the immune response and inhibiting the adhesion and invasion of pathogens [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%